Penentuan Debit Aliran Berbasis Data Satelit GPM pada Daerah Tangkapan Air (Studi Kasus: Waduk Sepaku Semoi) - Maknun, Dillon Asmara; suripin, Suripin (Department of Civil Engineering, Diponegoro University, 2023)
Sepaku Semoi Reservoir is located in Tengin Baru Village, Sepaku District, North Penajam Paser Regency, East Kalimantan Province, and has a water catchment area of 70.19 km2. This research aims to determine the amount of flow discharge entering the Sepaku Semoi Reservoir Catchment Area using the Mock Method. The rain data used is GPM satellite data as an alternative to the unavailability of rain recording posts in the Sepaku Semoi Reservoir Water Catchment Area. GPM satellite data needs to be calibrated and validated against rain recording posts in the field to determine the accuracy of the data. The highest GPM satellite data calibration is the Intercept linear regression equation with a value of R2 = 0.852. The best validation of GPM satellite data was shown in the 2004 period with a value of RMSE=65.04; KR=13%; R=0.91. The annual average maximum discharge is 6.26 m3/sec and the minimum is 3.17 m3/sec. Validation of the Mock Method flow rate is shown with a value of NSE=0.78; R=0.79. Based on the results of the analysis that has been carried out, concluded that an alternative in predicting observed discharge data in the field can be done using the Mock Method based on GPM satellite data.